Tiptoeing on Metastatic Adenocarcinoma of the Lung - Arupreet Kochar; Harrison D. Winters; Li Zhang; Bin Zhang; Kamia Thakur; Rajesh Essrani (Case Reports in Oncological Medicine)
Lung cancer remains the top cause of cancer-related death in the United States. Metastases to the distal phalanges are rare. This case illustrates an interesting presentation of metastatic adenocarcinoma of the lung that was mistaken for a benign condition of the toe.